Iron deficiency anemia and the risk of new-onset tinnitus in female patients: a cohort study - Hung, Kuo-Chuan; Weng, Hsiu-Lan; Lai, Yi-Chen; Lin, Yao-Tsung; Wu, Jheng-Yan; Lin, Chien-Hung; Chen, I-Wen (Frontiers in Nutrition, 2025)
BackgroundIron deficiency anemia (IDA) may compromise auditory function through cochlear hypoxia and altered hemodynamics; however, longitudinal evidence linking IDA to tinnitus remains limited. This study investigated the association between IDA and new-onset tinnitus in female patients using a large-scale cohort design.MethodsThis retrospective cohort study utilized the TriNetX electronic health records network (2010–2022) to identify female patients with and without IDA, focusing exclusively on women to minimize occupational noise exposure confounding. We defined IDA as hemoglobin below 12 g/dL and ferritin below 30 ng/mL recorded within 3 months, while controls had levels above these thresholds. The primary outcome was new-onset tinnitus, and the secondary outcome was pulsatile tinnitus, both assessed at 1 and 3 years after the index date. After employing propensity score matching to balance baseline characteristics, we calculated the hazard ratio (HR) using Cox proportional hazards models and performed pre-specified subgroup analyses examining dose-response relationships by hemoglobin severity and age-stratified effects.ResultsIDA was associated with a significantly higher risk of tinnitus at 1 year (HR 3.78, 95% confidence interval [CI]: 2.60–5.50; incidence 15.7 vs. 4.2 per 10,000 person-years) and at 3 years (HR 2.52, 95% CI 2.11–3.02; 18.6 vs. 7.4 per 10,000 person-years). Pulsatile tinnitus risk was similarly elevated at 3 years (HR 2.25, 95% CI 1.42–3.57). A clear dose-response relationship emerged, with severe IDA (hemoglobin < 10 g/dL) conferring highest 1-year risk (HR 5.74, 95% CI 3.24–10.16). Age-stratified analysis revealed differential vulnerability: older women (> 45 years) showed greater susceptibility to general tinnitus (HR 4.55 vs. 3.26), while younger women demonstrated exclusive risk for pulsatile tinnitus.ConclusionIDA showed a significant dose-dependent association with new-onset tinnitus in women. These findings support routine IDA screening in women presenting with tinnitus and suggest that timely iron repletion may help reduce the risk of potentially preventable auditory dysfunction.